USE OF A CONVOLUTION METHOD AT LINEAR INTERVALS IN X-RAY DIFFRACTION PROFILES. - RODRÍGUEZ-HERRERA, D. M.; PENTON-MADRIGAI, A.; ESTEVEZ-RAMS, E. (Revista Cubana de Física, 2024)
A mathematical formalism for calculating the intrinsic profile of a diffraction maximum through a convolution process using a set of linear functions by intervals is presented. This convolution process is implemented in the formalism for the direct solution of a diffraction pattern of a layered crystalline structure affected by planar defects. It allows the correlation length (AC) to be calculated, which describes the degree of disorder in this type of crystalline structure. The obtained result is validated through the Warren-Averbach method for microstructural analysis.